Identifying common baseline clinical features of COVID-19: a scoping review - Matilde Monteiro-Soares; Daniela Ferreira-Santos; Priscila Maranhão (BMJ Open)
Objectives Our research question was: what are the most frequent baseline clinical characteristics in adult patients with COVID-19? Our major aim was to identify common baseline clinical features that could help recognise adult patients at high risk of having COVID-19.Design We conducted a scoping review of all the evidence available at LitCovid, until 23 March 2020.Setting Studies conducted in any setting and any country were included.Participants Studies had to report the prevalence of sociodemographic characteristics, symptoms and comorbidities specifically in adults with a diagnosis of infection by SARS-CoV-2.Results In total, 1572 publications were published on LitCovid. We have included 56 articles in our analysis, with 89% conducted in China and 75% containing inpatients. Three studies were conducted in North America and one in Europe. Participants’ age ranged from 28 to 70 years, with balanced gender distribution. The proportion of asymptomatic cases were from 2% to 79%. The most common reported symptoms were fever (4%–99%), cough (4%–92%), dyspnoea/shortness of breath (1%–90%), fatigue (4%–89%), myalgia (3%–65%) and pharyngalgia (2%–61%), while regarding comorbidities, we found cardiovascular disease (1%–40%), hypertension (0%–40%) and cerebrovascular disease (1%–40%). Such heterogeneity impaired the conduction of meta-analysis.Conclusions The infection by COVID-19 seems to affect people in a very diverse manner and with different characteristics. With the available data, it is not possible to clearly identify those at higher risk of being infected with this condition. Furthermore, the evidence from countries other than China is, at the moment, too scarce.